Conotruncal heart defect/microphthalmia syndrome: delineation of an autosomal recessive syndrome. Issue 11 (November 1997) - Digilio, M C; Marino, B; Giannotti, A; Dallapiccola, B
Abstract : We report on three sibs born to healthy parents, one livebirth and two terminated pregnancies, presenting with a malformation complex characterised by conotruncal heart defect (CTHD), microphthalmia, genital anomalies, and facial dysmorphism. The recurrence of the association of CTHD, particularly truncus arteriosus, and microphthalmia in sibs has previously been reported in rare instances, but a correlation between the single descriptions has never been noted. CTHDs are included among the cardiac malformations characteristically associated with the group of syndromes caused by the microdeletion of chromosome 22q11, but no detectable hemizygosity has been found in our family. An autosomal recessive gene seems to be involved in syndromic patients with the combination of CTHD and microphthalmia. The map location of this gene is at present unknown, but autosomal recessive inheritance must be considered in genetic counselling of families with children presenting with this malformation complex.